Homeostatic Efficacy of Microporous Polysaccharide Hemosphere in Post-Operative Complications Reduction of Tubeless Percutaneous Nephrolithotomy - Seyed Mohammad Kazem Aghamir (Urology Research Center, 2020)
Introduction Current hemostatic agents are needed to reduce bleeding and transfusion during several surgery processes. Plant-based absorbable surgical hemostatic agents (microporous polysaccharide hemospheres) are proposed for use in surgical wound sites as an absorbable hemostat and in this study, we checked its efficacy. Methods This study was run under the Tehran University of Medical Science Ethics Committee observation based on the clinical trial registry criteria (IRCT20190624043991N1). Total numbers of 42 percutaneous nephrolithotomies (PCNL) patients were enrolled, 21 cases hemostatic powder and 21 controls. Hemostatic powder pumped into Amplatz sheath before its extraction. Results The mean age of the case and control groups was 42.1±19.5, and 42.1±18.5 years, respectively. The median stone size was 11.3±1.85cm. Overall, the differences between sex, age, stone size, and location were not statistically significant in the two groups (p-value˃0.05). Serum hemoglobin reduction following PCNL was significant in both groups compared to the serum level before surgery (p-value<0.001). However, the difference was not significant between case and control groups postoperatively (p-value=0.727). Yet, postoperative serum creatinine reduction was not significantly different between the two groups compared to preoperative serum levels (p-value>0.05). Conclusions The present study showed that microporous polysaccharide hemosphere (MPH) did not affect bleeding reduction, hemoglobin decline, and postoperative blood transfusion, and hospital stay.